MO321THE USE OF INTRAVENOUS CYCLOPHOSPHAMIDE AND ORAL STEROIDS IN PRIMARY MEMBRANOUS NEPHROPATHY WITH ADVANCED KIDNEY DISEASE. (29th May 2021) - Ragy, Omar; Hamilton, Patrick; Kanigicherla, Durga
Abstract: Background and Aims: International guidelines do not recommend specific use of immunosuppression treatment in membranous nephropathy patients presenting with an estimated glomerular filtration rate of <30ml/min/1.73m2. This is due to the scant published evidence of effectiveness and uncertainty around toxic effects at this stage. In this study, we sought to examine the safety and effectiveness of combined cyclophosphamide and steroids in primary membranous nephropathy with advanced kidney disease. Method: This is a retrospective study of 18 patients with a biopsy confirmed membranous nephropathy who received combination therapy between 2004 and 2019. The mean age was 66.5 with a 5:1 male: female ratio. The immunosuppression regime included monthly intravenous pulse cyclophosphamide and daily oral steroids. All patients had an initial eGFR of < or = 30 ml/min/1.73 m2 at time of treatment. Clinical parameters are serially monitored as part of clinical care and anti-PLA2R antibody levels were measured at the time of and 1-year post immunosuppression treatment where available. The primary outcome was the achievement of partial remission as per standard criteria. Secondary outcomes were immunological response defined by following the anti-PLA2R antibody levels at the time of presentation and 1-year post, need for renal replacement therapy, outcomes including hospital admission, infections, malignancy, and death. Results: Partial Remission was achieved in 16 out of 18 (88%) patients.7 patients (39%) reached complete remission, with none of them requiring dialysis over an average follow-up of 5 years. The average increase in eGFR was 12.5 ml/min/1.73m2 from the time of immunosuppression till the latest follow up. 2 out of 18 (11%) patients were refractory to treatment and required initiation of dialysis 1 and 8 years post immunosuppression. Results for the anti-PLA2R antibody test were available for 12 (66.6%) patients at presentation all shown to be positive. Of these, 7 (58%) achieved both immunological and clinical remission. 4 patients developed 4 different cancers (Bladder, mesothelioma, skin SCC and sigmoid) during follow-up; 2 patients required hospital admission for episodes of infections. Both were managed with antibiotics, and patients were discharged home safely. 5 patients died at the end of the follow-up period (27.7%). Conclusion: Here we show that the combination of intravenous pulse cyclophosphamide and steroid is well tolerated and effective in achieving remission in primary membranous nephropathy with advanced renal disease. Both immunological and clinical responses could be achieved in this cohort. Longer-term risk in such patients includes malignancy and infections. This study provides reassurance that this cohort of patients can be considered for immunosuppressive treatment, although prospective studies are required to provide further robust evidence.